Leveraging Relationship Marketing and Digital Engagement to Enhance Operational Efficiency in Indonesia’s Logistics Sector - Eka Pratiwi Septania Parapat (Journal of Innovative and Creativity (Joecy), 2026)
The rapid growth of Indonesia’s logistics sector necessitates innovative strategies to improve operational efficiency amid complex supply chain dynamics. This study examines the combined impact of relationship marketing and digital engagement on logistics performance, drawing on primary data from 120 logistics firms across Java and Sumatra. Using structural equation modeling, we assess how customer-centric relationship-building practices such as trust development, personalized communication, and loyalty programs interact with digital engagement initiatives, including real‐time tracking, social media interaction, and mobile platforms, to influence cost reduction, delivery reliability, and process agility. Results reveal that relationship marketing exerts a direct positive effect on operational efficiency (β = 0.45, p < 0.01), while digital engagement mediates this relationship, amplifying efficiency gains by 30%. Integrating digital tools into customer relationship frameworks enhances transparency, responsiveness, and collaborative decision‐making. The findings provide empirical support for a unified strategic approach, highlighting that synergistic implementation of marketing and digital technologies can drive sustainable competitive advantage in emerging‐market logistics.